1980
DOI: 10.1001/jama.1980.03310060038020
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Routine Preoperative Chest Roentgenograms in Infants and Children

Abstract: The charts and routine preoperative roentgenograms of 350 children admitted for elective pediatric surgery were analyzed to evaluate the clinical importance of routine preoperative chest roentgenograms. This analysis, and a review of the literature, should indicate that routine preoperative roentgenograms for elective pediatric surgery are unnecessary. Indications for selected preoperative roentgenograms based on patients' history and clinical findings are enumerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…These conclusions were reached on the basis of numerous study results (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) that showed thoracic radiography to have low diagnostic yield in asymptomatic hospitalized patients, both in the United States and abroad. Despite these findings, it was estimated that in 1980, 30 million of the 52 million chest radiographs obtained in hospitalized patients in the United States were routine or admission images (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These conclusions were reached on the basis of numerous study results (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) that showed thoracic radiography to have low diagnostic yield in asymptomatic hospitalized patients, both in the United States and abroad. Despite these findings, it was estimated that in 1980, 30 million of the 52 million chest radiographs obtained in hospitalized patients in the United States were routine or admission images (6).…”
mentioning
confidence: 99%
“…Previous studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) have been restricted to hospitalized patients or narrowly defined groups such as pregnant women, individuals with asthma, and patients undergoing psychiatric treatment. The purpose of our study, however, was to determine the frequency, diagnostic yield, costs, and rate of false-positive results of routine chest radiography performed in asymptomatic primary care patients.…”
mentioning
confidence: 99%